Foot adaptations in four species of Whistling Duck Dendrocygna - Bolen, Eric G; Rylander, M Kent (Wildfowl, 1974)
A comparison of the mid-toe and tarsus proportions for two geographical pairs of whistling ducks Dendrocygna spp. shows that each pair contains one member with disproportionately larger feet. These species, D. bicolor and D. arcuata, have highly aquatic habits whereas the other members of each pair (D. autumnalis and D. eytoni respectively) are far less aquatic and exhibit cursorial habits. In the latter case, the similarities in foot sizes suggest an instance of parallel evolution that is strongly supported by phenetic analysis of other characteristics.